JHU-2545 preferentially shields salivary glands and kidneys during PSMA-targeted imaging. - Nedelcovych, Michael T.; Dash, Ranjeet P.; Wu, Ying; Choi, Eun Yong; Lapidus, Rena S.; Majer, Pavel; Jančařík, Andrej; Abou, Diane; Penet, Marie-France; Nikolopoulou, Anastasia; Amor-Coarasa, Alex; Babich, John; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: Prostate-specific membrane antigen (PSMA) radioligand therapy is a promising treatment for metastatic castration-resistant prostate cancer (mCRPC). Several beta or alpha particle-emitting radionuclide-conjugated small molecules have shown efficacy in late-stage mCRPC and one, [[177Lu]Lu]Lu-PSMA-617, is FDA approved. In addition to tumor upregulation, PSMA is also expressed in kidneys and salivary glands where specific uptake can cause dose-limiting xerostomia and potential for nephrotoxicity. The PSMA inhibitor 2-(phosphonomethyl)pentanedioic acid (2-PMPA) can prevent kidney uptake in mice, but also blocks tumor uptake, precluding its clinical utility. Preferential delivery of 2-PMPA to non-malignant tissues could improve the therapeutic window of PSMA radioligand therapy. Methods: A tris(isopropoxycarbonyloxymethyl) (TrisPOC) prodrug of 2-PMPA, JHU-2545, was synthesized to enhance 2-PMPA delivery to non-malignant tissues. Mouse pharmacokinetic experiments were conducted to compare JHU-2545-mediated delivery of 2-PMPA to plasma, kidney, salivary glands, and C4-2 prostate tumor xenograft. Imaging studies were conducted in rats and mice to measure uptake of PSMA PET tracers in kidney, salivary glands, and prostate tumor xenografts with and without JHU-2545 pre-treatment. Results: JHU-2545 resulted in approximately 3- and 53-fold greater exposure of 2-PMPA in rodent salivary glands (18.0 ± 0.97 h*nmol/g) and kidneys (359 ± 4.16 h*nmol/g) versus prostate tumor xenograft (6.79 ± 0.19 h*nmol/g). JHU-2545 also blocked rodent kidneys and salivary glands uptake of the PSMA PET tracers [68Ga]Ga-PSMA-11 and [18 F]F-DCFPyL by up to 85% with little effect on tumor. Conclusions: JHU-2545 pre-treatment may enable greater cumulative administered doses of PSMA radioligand therapy, possibly improving safety and efficacy. Key points: Question: Is there a method of limiting PSMA radioligand uptake into salivary glands and kidneys to potentially mitigate associated toxicity without hindering tumor uptake/efficacy? Pertinent findings: JHU-2545, a prodrug of the PSMA inhibitor 2-PMPA, was found to preferentially deliver 2-PMPA to salivary glands and kidneys relative to tumor xenografts in rodent models, leading to blunted uptake of PSMA radioligands in non-tumor tissues. Implications for patient care: If replicated in clinical studies, JHU-2545 could reduce radiation doses to salivary glands and kidneys and possibly mitigate associated toxicities in prostate cancer patients receiving PSMA radioligand therapy.